ACTUALIZATION OF SPIRITUAL WORKPLACE VALUE AT AMIL ZAKAT INSTITUTION (DOMPET DHUAFA YOGYAKARTA) - Muhammad Mujib Baidhowi (Tasharruf: Journal Economics and Business of Islam, 2020)
As a public finance institution, Dompet Dhuafa is one of the zakat management organization that has a significant development every year. Such development surely is correlated to the increasing quality of Human Resources. Spiritual Workplace is a new concept in management and organizational behavioral model, especially organizational culture that can show the construction of quality in work performance improvement. This study aims to describe and analyze the tithe (zakat) management of Dompet Dhuafa and analyze the actualization of Spiritual Workplace in Dompet Dhuafa Yogyakarta. This is field research with and the qualitative descriptive analysis method. A phenomenological approach was used with the consideration that this approach could produce data in the form of speech, writing, and treatment of the people observed. Based on the results of the research it can be figured out that overall the tithe management in Dompet Dhuafa Yogyakarta is divided into two parts: collection and utilization in which both have some supporting programs in the development of tithe management. Meanwhile, the indicators of the spiritual building in the workplace including Connection, Compassion, Mindfulness, Meaningful Work, and Transcendence have not been achieved comprehensively, yet the routines run in Dompet Dhuafa Yogyakarta have reflected the spiritual workplace. Quality improvement was always done enabling the funds received from the community to be managed properly in accordance with the principles of the fund management of zakat, infaq, and sadaqah.